Flagellar preparations from Pseudomonas aeruginosa: isolation and characterization. - Montie, T C (1982)
Flagella from various strains of Pseudomonas aeruginosa were isolated by shearing the flagella followed by differential centrifugation to obtain typical filaments as viewed through an electron microscope. Electrophoretic analysis showed a major protein band corresponding to a flagellin with molecular weight of 53,000. Among the strains tested, flagellar antigen (FAg) preparations isolated from strains 1244 and 1210 routinely gave the highest percentage of flagellin, with the least amount of protein impurities, when grown on succinate-mineral salts medium. All FAg preparations contained 3 to 10 micrograms of 2-keto-3-deoxyoctonate-positive material per mg of protein. Strain PA-103 lacked flagella and exhibited no flagellin band, and preparations from PA-103 had a relatively higher content of 2-keto-3-deoxyoctonate. The isolation of highly purified, single-banded flagellin could be accomplished by elution of the 53,000-molecular weight gel band. Amino acid analysis showed 16 amino acids, but no proline. Antisera to FAg preparations were used to demonstrate inhibition of motility of strains RM-46 and M-2. Heated RM-46 FAg antisera and PA-103 antisera did not inhibit motility.